Caracterização de fácies e análise de proveniência de um afloramento da formação Morro do Chaves na sub-bacia de Sergipe - Andrade, Larissa Lins (DGEOL - Departamento de Geologia – São Cristóvão - Presencial, 2018)
The Sergipe-Alagoas basin is related to the break-up of the Gondwana Superconinent and the onset of the opening of the South Atlantic Ocean. The basin records all evolutive sequences: sineclises, pre-rift, rift, pos-rift and passive margin. The Morro do Chaves Formation, object of this work comprises a small part of the rift sequence, composed of carbonate rocks, shales, sandstones and conglomerates, interpreted as the product of a carbonate shelf fed by alluvial fan deposits. Although previous interpretations regarding the paleoenvironment is not a matter of concern, one question is still under debate, and concerns the setting of structural highs troughout the rift phase, which could have controlled the distribution of source rocks over the adjacent rift shoulders. The inference of source rocks along the adjacent footwall could help to understand the extension in area of the watershed that fed the basin during its early stage of formation in the lower cretaceous. In order to discuss and contribute to this issue, facies and provenance analyses were applied on one outcrop of the Morro do Chaves Formation, located at the city of Propriá. The results from facies analysis allowed to interpret three facies associations (AF1, AF2 and AF3). AF1 is related to a continental settling, dominated by alluvial fans. AF2 suggests the deposition under a lake environment with secondary contribution of alluvial fans, influenced by wave action. AF3 was interpreted as a deeper lake phase non influenced by current waves or gravitational flows. Provenance analysis showed a major contribution of quartzite and vein quartz pebbles and the prevalence of sub-angulous and angulous lithoclasts, which suggest a local source area, probably at the Macururé Domain. The less contribution of granites lithoclasts from the bottom to top of the stratigraphic section studied indicate a progressive denudation of the basement rocks as the the rift shoulder was uplifted. Although this model is still preliminary, it implies that capture drainage basins ...